1977
DOI: 10.1007/bf00034986
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of exogenous proteolytic enzymes in digestion processes in fish

Abstract: Studies were carried out on the proteolytic activity of the fry of common carp, rainbow trout, grass carp, and whitefish, as well as on the activity of digestive organs of adult common carp and rainbow trout . Activity of exogenous enzymes in relation to endogenous ones was assessed on the basis of the proteolytic value of fish food and the activity of digestive organs . It was found that the share of proteolytic enzymes of natural food in the digestion process in fish was high . Beginning from a weight of 50-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0
2

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 9 publications
8
65
0
2
Order By: Relevance
“…Enzymes play an important role in the digestion and utilisation of feed (Dabrowski and Glogowski, 1977) and dietary nutrients influence digestive enzyme activity (Gangadhara et al, 1997;Fountoulaki et al, 2005). In general, the activity pattern of the digestive enzymes corroborated the digestibility pattern of nutrients in the diets in both the species tested.…”
Section: Discussionmentioning
confidence: 90%
“…Enzymes play an important role in the digestion and utilisation of feed (Dabrowski and Glogowski, 1977) and dietary nutrients influence digestive enzyme activity (Gangadhara et al, 1997;Fountoulaki et al, 2005). In general, the activity pattern of the digestive enzymes corroborated the digestibility pattern of nutrients in the diets in both the species tested.…”
Section: Discussionmentioning
confidence: 90%
“…O tratamento A+R proporcionou o melhor desempenho das larvas, demonstrando a importância da Artemia no início da alimentação exógena, devido ao seu alto valor biológico e pequeno tamanho, o que permita que seja o primeiro alimento ingerido pelas larvas, como constatado por Kossowski (1991 O menor desempenho final das larvas do tratamento Z demonstra que apesar de inicialmente o desenvolvimento ser satisfatório, pelo fato do zooplâncton ser um alimento de alto valor biológico e liberar enzimas proteolíticas (DABROWSKI;GLOGOWSKI, 1977;HERBERT, 1978), com o desenvolvimento das larvas, estas passaram a ter preferência pelos alimentos inertes (UFODIKE; WADA, 1991).…”
Section: Resultsunclassified
“…Thus t increased levels of digestive enzymes were presumed to be induced by feeding on living organisms. Dabrowski and Glogowski (1977) have suggested that larval marine fishes require an exogenous source of digestive enzymes from a live, or at least natural, food in order for " enzyme secretion to function properly since initially the gastrointestinal cells were not completely differentiated. Whether a similar induction of specific digestive enzymes by exogenous substrate or enzyme molecules occurs in invertebrate larvae is unknown.…”
Section: Values Expressed Are Mean±8tandard Deviation (0=3)mentioning
confidence: 99%